The perceived usefulness of community based education and service (COBES) regarding students' rural workplace choices. Issue 1 (December 2016) - Amalba, A.; van Mook, W.; Mogre, V.; Scherpbier, A.
Abstract Background Community Based Education and Service (COBES) are those learning activities that make use of the community as a learning environment. COBES exposes students to the public and primary health care needs of rural communities. The purpose of this study was to investigate students' perceived usefulness of COBES and its potential effect on their choice of career specialty and willingness to work in rural areas. Method A mixed method cross sectional study design using semi-structured interviews, questionnaires, and focus group discussions were used for health facility staff, faculty and students and community members. Results One hundred and seventy questionnaires were administered to students and 134 were returned (78.8 % response rate). The majority (59.7 %) of students were male. Almost 45 % of the students indicated that COBES will have an influence on their choice of career specialty. An almost equal number (44 %) said COBES will not have an influence on their choice of career specialty. However, 60.3 % of the students perceived that COBES could influence their practice location. More males (64.7 %, n = 44) than females (57.8 %, n = 26) were likely to indicate that COBES will influence their practice location but the differences were statistically insignificant (p = 0.553). The majority of students, who stated that COBES could influence their practice location, said that COBES may influence them to choose to practice in the rural area and that exposure to different disease conditions among different population groups may influence them in their career choice. Other stakeholders held similar views. Qualitative data supported the finding that COBES could influence medical students' choice of specialty and their practice location. Conclusion Medical students' 'perceptions of the influence of COBES on their choice of career specialty were varied. However, most of the students felt that COBES could influence them to practice in rural locations.